Multifeed tri‐band circularly polarized antenna for UHF/MW‐RFID application. Issue 1 (12th October 2021) - Zhang, Enze; Michel, Andrea; Nepa, Paolo; Qiu, Jinghui
Abstract: A compact three‐port tri‐band circularly polarized (CP) antenna for radio‐frequency identification (RFID) technique is introduced. Four inverted‐F radiating elements fed with a 90° phase delay feeding network realize the CP radiation at the FCC UHF‐RFID band (0.902–0.928 GHz). With the slot‐coupled feeding technique, Corner‐truncated slot and patch have been employed to achieve CP radiation at MW‐RFID bands (2.4–2.485/5.725–5.875 GHz). Decoupling structures are implemented to obtain excellent 20 dB port isolations during all operating bands. The relative impedance bandwidths in the three bands are 6.6%, 5.3%, and 5.1%, respectively, with peak gains of 2, 5.1, and 5.7 dBic.